2021
DOI: 10.1177/08903344211058373
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Professionals’ Breastfeeding Attitudes and Hospital Practices During Delivery and in Neonatal Intensive Care Units: Pre and Post Implementing the Baby-Friendly Hospital Initiative

Abstract: Background: The Baby-Friendly Hospital Initiative represents a global effort to support breastfeeding. Commitment to this program has been associated with the longer duration and exclusivity of breastfeeding and improvements in hospital practices. Further, healthcare professionals’ breastfeeding attitudes have been associated with the ability to provide professional support for breastfeeding. Research Aims: To determine healthcare professionals’ breastfeeding attitudes and hospital practices before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Staff surveys carried out over time need to take account of turnover of staff, therefore longitudinal studies are recommended [ 116 ]. Mäkelä et al [ 152 ] also emphasised the need to study the sustainability of achieved changes in practice, based on a study in Finland, as did a study in the USA [ 153 ]. Shing et al [ 122 ] highlighted the need to consider wider cultural changes about breastfeeding, when conducting longitudinal studies.…”
Section: Resultsmentioning
confidence: 99%
“…Staff surveys carried out over time need to take account of turnover of staff, therefore longitudinal studies are recommended [ 116 ]. Mäkelä et al [ 152 ] also emphasised the need to study the sustainability of achieved changes in practice, based on a study in Finland, as did a study in the USA [ 153 ]. Shing et al [ 122 ] highlighted the need to consider wider cultural changes about breastfeeding, when conducting longitudinal studies.…”
Section: Resultsmentioning
confidence: 99%
“…In societies where breastfeeding is a norm and the Ten Steps practices are incorporated into the routine care, differences between Baby-Friendly hospitals and non-Baby-Friendly hospitals may be small (Brodribb et al, 2013). On the other hand, a previous study has shown that BFHI implementation is positively associated with healthcare professional's breastfeeding attitudes and breastfeeding support practices in birth hospital (Mäkelä et al, 2021). Based on this, it is likely that mothers in Baby-Friendly hospitals do perceive support that is more adherent to the Ten Steps practices, compared to mothers in non-Baby-Friendly hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…When we discuss the impact of pacifiers and bottles on breastfeeding, the most important outcome is direct breastfeeding, but many studies have also used breastmilk feeding. The BFHI has increased the breastmilk feeding rate 9 in all income settings 10,11 and improved staff attitudes to breastfeeding 12 . However, some studies have also reported downsides to the BFHI, such as increases in hypoglycaemia cases or prolonged hospital stays, although these findings could also have been due changed treatment guidelines 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The BFHI has increased the breastmilk feeding rate 9 in all income settings 10,11 and improved staff attitudes to breastfeeding. 12 However, some studies have also reported downsides to the BFHI, such as increases in hypoglycaemia cases or prolonged hospital stays, although these findings could also have been due changed treatment guidelines. 13,14 It should also be noted that hygiene and clean water resources may be limited globally and may lead to increased risk of infections in neonates and infants if bottles and pacifiers cannot be cleaned adequately.…”
Section: Introductionmentioning
confidence: 99%